Differential patterns of gene expression associated with microsatellite instability and chromosomal instability in colorectal cancer - Dunican, Donncha St. John (Trinity College (Dublin, Ireland). School of Biochemistry and Immunology, 2000)
Two distinct pathways exist in sporadic colorectal cancer. The microsatellite instability pathway (MIN) is recognised by widespread instability caused by aberrant mismatch repair machinery. This genotype accounts for 15% of sporadic colorectal cancers. The chromosomal instability (CIN) genotype is recognised by gross chromosomal lesions but the underlying mechanism of CIN remains unclear. The differences in MIN and CIN colon cancer are likely to be due to the coordinate activation and repression of a key number of genes. Identitication of MIN and CIN targeted genes will increase our understanding of the presence of two distinct genotypes in one type of cancer.
Keywords: Biochemistry, Ph.D.; Ph.D. Trinity College Dublin